The value of applied economics the life and work of Arthur - Button, Kenneth (Northampton Edward Elgar Pub, 2017)
This biography of the applied English economist Arthur (A.J.) Brown, an English economist from the late 1930s to the 1980s, sets his work in the context of the Great Depression, the emergence of Oxford University as centre of applied economic research, the contraction of British colonialism in Africa, the enlarging of the UK university system, the post-war arms race, the UK joining the Common Market, and significant changes in the industrial structure of Britain.
ix, 406 p. ; 24 cm.
Keywords: Marx, Karl, 1818-1883; Anarchism; Anarchists